3(-2)=-9y+33

Simple and best practice solution for 3(-2)=-9y+33 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(-2)=-9y+33 equation:


Simplifying
3(-2) = -9y + 33

Multiply 3 * -2
-6 = -9y + 33

Reorder the terms:
-6 = 33 + -9y

Solving
-6 = 33 + -9y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '9y' to each side of the equation.
-6 + 9y = 33 + -9y + 9y

Combine like terms: -9y + 9y = 0
-6 + 9y = 33 + 0
-6 + 9y = 33

Add '6' to each side of the equation.
-6 + 6 + 9y = 33 + 6

Combine like terms: -6 + 6 = 0
0 + 9y = 33 + 6
9y = 33 + 6

Combine like terms: 33 + 6 = 39
9y = 39

Divide each side by '9'.
y = 4.333333333

Simplifying
y = 4.333333333

See similar equations:

| 10k+7-3k-11= | | 5x-8y-15=0 | | 3x=-9(6)+33 | | 3(5)=-9y+33 | | 8a-1.5=3a-7 | | 3y-12=4y+88 | | C=50(215)+40 | | 1.5=50n+40 | | 2=50n+40 | | T=L(4+RS) | | 5(x-3)+4=2(x-4) | | 12x^2+17x-7=0 | | 5x+10=2(2x+5) | | (2a/3)+(7a/9)+2=0 | | 4y-20= | | -3kx^2+4x^2+26x-17=0 | | 11=x-4 | | 4a+13-a+7=7a+10+2-a | | 3x^2+5x-50=0 | | 11x=90-7x | | 12z/3=z-6 | | x-3/5=-1/2 | | 5y-3(y-2)+4= | | 55=(x+25) | | 5x+12=7x-8 | | 20+5x=4(x-3) | | 4x+10=100 | | 9y-47=y+73 | | 105+(3x-18)=180 | | 0=x^2+12x-6 | | -5(2+3)+3z= | | 5(y+4)=6(y-4) |

Equations solver categories